PEMBERDAYAAN MOJOREJO: SEBUAH INISIATIF PENGABDIAN MASYARAKAT DI KAMPUNG PANCASILA - Atiek Rohmiyati; Wahyu Suwarni (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
Many people still do not understand what is meant by Pancasila from its origins, the meaning of Pancasila and the values in life in the nation, state and society. Initially, the TNI, which had the ambition to form a Pancasila village in Mojorejo Village, Jetis District, Ponorogo Regency, East Java, has been formed into a Pancasila village. The problem faced in Mojorejo village is that since the formation of the Pancasila village, there has been no socialization about the program activities in the Pancasila village. The goal is to provide the community of Mojorejo village, Jetis District so that the community understands the meaning of Pancasila values in community life. The method in this service begins with a survey in Mojorejo Village, conducting a comparison with the Pancasila village in Bekasi. Interviews with village officials (village secretary), Submitting a service permit letter, a reply letter permitting service in Mojorejo Village, implementation of service by providing counseling. Then make a report. The result is that the village officials and PKK mothers of Mojorejo village understand the practice of Pancasila values which are not focused on just one principle but the five principles can be implemented in family, community and village officials in carrying out village management activities in Pancasila villages both in deliberation, and policy making, as well as managing the village economy.